Converged stepped spillway models in OpenFOAM - Sweeney, Brian P. (Kansas State University, 2014)
The United States Department of Agriculture (USDA) is currently researching the effectiveness of various earth dam designs and their ability to prevent erosion. This report utilizes experimental results from the USDA experimental hydraulic engineering research unit to develop computational fluid dynamics models using OpenFOAM. Several variations of smooth and stepped dam models are created and analyzed with OpenFOAM on multiple cores using Message Passing Interface. In this report, seven dam designs are analyzed to extract flow velocities and pressures and animations. This data and OpenFOAM models are helpful for determining potential erosion conditions.
Keywords: OpenFOAM; Earth dam; Overtopping; Computer Science (0984); Hydrologic Sciences (0388)